REKONSTRUKSI OTORITAS SUNAH DI ERA MODERN: ANALISIS KRITIS ATAS PEMIKIRAN DANIEL W. BROWN - Sugeng, Laksamana Naufal Hadi; Nurhaliza Oktaviani Z (IAIN KENDARI, 2025)
This study examines Daniel W. Brown’s thought in Rethinking Tradition in Modern Islamic Thought to map the epistemological evolution of the Sunnah from an early living tradition within the Muslim community to a rigid textual construct following al-Shafi‘i’s codification. Using a qualitative descriptive method through content analysis of Brown’s work and supporting literature, the study finds that contemporary debates between textualist and contextualist approaches are a continuation of classical tensions in the history of Islamic law. Brown emphasizes the need to distinguish the universal moral values of the Sunnah from the Prophet’s context-specific practices and highlights the importance of revitalizing matn criticism so that the Sunnah is not reduced to a rigid normative corpus but remains relevant to modern challenges. The study concludes that Brown’s historical-critical framework provides a significant foundation for reconstructing a more balanced understanding of the Sunnah, although further research is needed to develop a more operational and reconstructive methodology.